2021
DOI: 10.1186/s12890-021-01773-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and detection of pathogenic bacteria from patients with hospital-acquired pneumonia in southwestern Iran; evaluation of biofilm production and molecular typing of bacterial isolates

Abstract: Background Hospital-acquired pneumonia (HAP) is the second most common nosocomial infection in intensive care units (ICUs). The present study aims to determine the prevalence of pathogenic bacteria, their biofilm formation, and molecular typing from patients with HAP in southwestern Iran. Methods Fifty-eight patients with HAP participated in this cross-sectional study. Sputum and endotracheal aspirate were collected from each patient for isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…A study conducted on Egyptian children revealed that GNB was more prevalent in HAP and VAP (91.67 and 87.8%, respectively) [ 49 ]. In Iran, GNB was obtained in 72.2 and 84.6% of HAP and VAP, respectively [ 50 ]. Feng et al [ 51 ] reported a 14.5% mortality rate of HAP related to GNB in a retrospective, single-center analysis study in China.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on Egyptian children revealed that GNB was more prevalent in HAP and VAP (91.67 and 87.8%, respectively) [ 49 ]. In Iran, GNB was obtained in 72.2 and 84.6% of HAP and VAP, respectively [ 50 ]. Feng et al [ 51 ] reported a 14.5% mortality rate of HAP related to GNB in a retrospective, single-center analysis study in China.…”
Section: Introductionmentioning
confidence: 99%
“…A. baumannii is one of the most common bacteria detected in sputum culture and endotracheal aspirate from long-term hospitalized patients, including those with HAP. 3 A. baumannii is an opportunistic infectious agent that can cause lung infection and nosocomial infection transmission. 12 It usually causes bacterial colonization, defined as the presence of bacteria on the body surface, including the airway, without causing clinical evidence of infection in the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter baumannii (A. baumannii) was the most prevalent organism, followed by Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa), and Escherichia coli (E. coli) from the sputum and endotracheal aspirates collected from each patient for bacterial isolation and detection. 3 A. baumannii infection often results in poor prognosis and high mortality. 4 In a multicenter retrospective cohort study, Ko RE found that A. baumannii was the most common multidrug-resistant (MDR) pathogen, leading to 28.2% of patients being admitted to the ICU for additional care and 28.1% dying.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of MRSA pneumonia is different, depending on the classification of pneumonia. For CAP, the prevalence of S. aureus is 1.8%, whereas in HAP or VAP, S. aureus is isolated in 15%–18% of the cases 2 3. The prevalence of S. aureus being methicillin-resistant ranges from 37% to 54.4%.…”
Section: Introductionmentioning
confidence: 99%